Penerapan Metode Vikor (Višekriterijumsko Optimizacija I Kompromisno Rangiranje) Untuk Rekomendasi Siswa Berprestasi Pada Smk Negeri 6 Kabupaten KaurApplication of Vikor Method (Višekriterijumsko Optimizacija I Kompromisno Rangiranje) for Recommendation o - Nopa, Apindo Waldi; Kanedi , Indra; Prahasti (CV. Generasi Insan Rafflesia, 2023)
In a school, the ranking of outstanding students is usually only selected based on their final grades, as well as at SMK 6 Kaur Regency. The selection of outstanding students at SMK 6 Kaur Regency is only based on report card grades. The selection process has many opportunities to make wrong decisions because the student selection process is only based on one aspect, namely the student's final grade, while the attitude and achievement scores obtained outside of school are not taken into consideration as additional criteria for determining students who are considered outstanding and get scholarships. This means that it is likely that the selected outstanding students do not reach the desired standards that do not obtain the best candidates. The purpose of this research is as an alternative way for schools to determine outstanding students so that they are not only based on academic grades, and there is no cheating in the selection of outstanding students. The method used in this research is the Vikor method (Višekriterijumsko Optimizacija I Kompromisno Rangiranje). The result of this research is that the Vikor method can provide the best results from the criteria and weights that have been determined. The results of this study show that the Vikor method can provide the best results from the criteria and weights that have been determined. From the calculation results with the Vikor method, a student named Alpikran was obtained with a preference value of 0.040.